Neural Correlates of Facial Mimicry: Simultaneous Measurements of EMG and BOLD Responses during Perception of Dynamic Compared to Static Facial Expressions - Rymarczyk, Krystyna; Żurawski, Łukasz; Jankowiak-Siuda, Kamila; Szatkowska, Iwona (Frontiers in Psychology, 2018)
Facial mimicry (FM) is an automatic response to imitate the facial expressions of others. However, neural correlates of the phenomenon are as yet not well established. We investigated this issue using simultaneously recorded EMG and BOLD signals during perception of dynamic and static emotional facial expressions of happiness and anger. During display presentations, BOLD signals and zygomaticus major (ZM), corrugator supercilii (CS) and orbicularis oculi (OO) EMG responses were recorded simultaneously from forty-six healthy individuals. Subjects reacted spontaneously to happy facial expressions with increased EMG activity in ZM and OO muscles and decreased CS activity, which was interpreted as facial mimicry. Facial muscle responses correlated with BOLD activity in regions associated with motor simulation of facial expressions (i.e., inferior frontal gyrus, a classical Mirror Neuron System (MNS)). Further, we also found correlations for regions associated with emotional processing (i.e., insula, part of the extended MNS). It is concluded that facial mimicry involves both motor and emotional brain structures, especially during perception of natural emotional expressions.